Operation Brain Trauma Therapy: An Exploratory Study of Levetiracetam Treatment Following Mild Traumatic Brain Injury in the Micro Pig - Lafrenaye, Audrey; Mondello, Stefania; Povlishock, John; Gorse, Karen; Walker, Susan; Hayes, Ronald; Wang, Kevin; Kochanek, Patrick M. (Frontiers in Neurology, 2021)
Operation Brain Trauma Therapy (OBTT) is a drug- and biomarker-screening consortium intended to improve the quality of preclinical studies and provide a rigorous framework to increase the translational potential of experimental traumatic brain injury (TBI) treatments. Levetiracetam (LEV) is an antiepileptic agent that was the fifth drug tested by OBTT in three independent rodent models of moderate to severe TBI. To date, LEV has been the most promising drug tested by OBTT and was therefore advanced to testing in the pig. Adult male micro pigs were subjected to a mild central fluid percussion brain injury followed by post-injury intravenous infusion of either 170 mg/kg LEV or vehicle. Systemic physiology was assessed throughout the post-injury period. Serial serum samples were obtained pre-injury, as well as at 1 min, 30 min, 1 h, 3 h and 6 h post-injury, for detailed analysis of the astroglial biomarker glial fibrillary acidic protein (GFAP) and ubiquitin carboxy-terminal hydrolase L1 (UCH-L1). Tissue was collected 6h following injury for histological assessment of diffuse axonal injury, using antibodies against amyloid precursor protein (APP). Animals showed significant increases in circulating GFAP levels from baseline to 6 h post-injury, however, LEV treatment was associated with greater GFAP increases compared to vehicle. There were no differences in the numbers of APP+ axonal swellings within the pig thalamus with LEV treatment, however, significant alterations in the morphological properties of the APP+ axonal swellings, including reduced swelling area and increased swelling roundness, were observed. Additionally, expression of the neurite outgrowth marker, growth associated protein 43 (GAP43) was reduced in axonal swellings following LEV treatment, suggesting potential effects on axonal outgrowth that warrant further investigation.